Partner of Choice: Australian National Interest in Infrastructure Development Programs in Papua New Guinea - Lucy Pennington (Asia & the Pacific Policy Studies)
ABSTRACT Australian‐funded development programs aim to support the needs of partner governments but ultimately advance Australiaʼs national interests. This research unpacks this discourse on the major Australian‐funded infrastructure development programs in Papua New Guinea. It has two key findings: first, the way program reporting speaks about geopolitics is implicit, while partnerships are made explicit. DFAT speaks between the lines on geopolitics in aid. Yet, external media and the aid community outside government bureaucracy are quick to speculate about links between the two. Second, political “goals” are achieved everywhere, and not through DFAT effort alone. In this dataset, individual advisers are a key vector of this under‐reported influence. They often perform as political actors despite their position outside formal aid structures. Ultimately, actors are aware of the many aims of the aid program yet seem to make only a certain portion explicit and visible, just to ensure things work in practice.